Experimental investigation into aircraft system manual assembly performance under varying structural component orientations. (March 2020) - Judt, David; Lawson, Craig; Lockett, Helen
Installation of aircraft wing systems is a bottleneck in the assembly process. This phase is typically composed of many work packages, taking hundreds of man-hours per wing. In addition to this volume of work, tasks are specialized and completed in a difficult environment in terms of access and visibility. In current industrial practice, the wing is mounted horizontally on a transport trolley, which exposes the workforce to prolonged periods of overhead working. Future wing designs may consider a pre-equipping build philosophy, where systems are installed to major structure assemblies before the wing box is assembled. This allows for a change in the orientation and position of the major structure and provides new freedoms in assembly station design and layout. This research presents results of experiments to investigate manual assembly performance of aircraft wing systems, under varying wing structure orientation. A mock-up of a section of an A320 aircraft wing front spar, mounted on a rotation device, functions as the testbed. Manual installation activities are then conducted to emulate real aircraft system equipping for electric harnesses, raceways and hot air ducts. The results show a best-case assembly performance change of 36% for electric system installation activities of cable harnesses and raceway housing components. Tilted and horizontal orientations of the structure show the highest time reductions, with the vertical orientation either non-conclusive or increasing the assembly time. The outcomes of this study are intended to aid in effective trade-off decision making for future wing systems and assembly station layouts from the perspective of structural orientation and assembly task interaction.